DIETARY EXPOSURE ASSESSMENT FOR AFLATOXIN B FROM PROCESSED PEANUT PRODUCTS IN MUNICIPALITY OF BOGOR 1 - OKKY SETYAWATI DHARMAPUTRA; SANTI AMBARWATI SANTI; INA RETNOWATI INA (SEAMEO BIOTROP, 2011)
A research on dietary exposure assessment for aflatoxin B (AFB1) fromprocessed peanutproducts in Municipality of Bogor was carried out. The objectives of this study were todetermine the contents of AFB1 in processed peanut products at retail levels, and to obtaininformation whether there is a risk to public health caused by the consumption of processedpeanut products contaminated by AFB1. Survey of processed peanut product consumptionwas carried out by interviewing each respondent using a questionnaire of weekly processedpeanut product consumption. Sampling of processed peanut products was conducted at thelocations where the respondents obtained processed peanut products. The number of roastedpeanuts with skin pods, flour-coated peanuts and or sauces samples was 33,respectively, while the number of and sauces samples was 18 and 12, respectively.The total number of processed peanut product sampleswas 129.AFB1contentwas determinedusingThin LayerChromatographymethod.Estimation of the dietary exposure assessmentwasdetermined using the actual survey data consisting of AFB1 content, consumption data andbody weight. The highest contaminated sample percentage and mean of AFB1 content wasfound in roasted peanuts with skin pods i.e. 42% of 33 samples and 43.2 Î¼g/kg, respectively,followed by flour-coated peanuts (30% of 33 samples and 34.3 Î¼g/kg), and or(21%of 33 samples and 17.1 Î¼g/kg).Mean of estimated dietary exposure for AFB1 found inchildren was 15.2 ng kg bw day and 95 percentile exposure was 38.9 ng kg bw day , while inadults 9.0 ng kg bw day and 95 percentile exposure was 27.0 ng kg bw day . The excesscancer risk of AFB1 exposure in Bogor fromthis study on children and adults was calculated as193 and 115 cancers/year, respectively-1 -1 th -1 -1-1 -1 th -1 -1pecel gado-gadosiomay sataipecel gado-gado1.